How central is central counterparty clearing? A deep dive into a European repo market during the crisis - André Ebner; Falko Fecht; Alexander Schulz (Deutsche Bundesbank, 2016)
Repo markets offering central counterparty (CCP) clearing and anonymized trading were remarkably resilient during the recent crises. We use the full transaction level dataset on all repo trades on Eurex Repo, including identifiers for market participants, to provide a detailed description of the market's development and microstructure during the crises and under different monetary policy interventions. Overall, we find high excess liquidity being associated with lower private liquidity provision in this market. Cross-segment arbitrage and market making is limited but growing steadily. The reallocation of liquidity risk across banks within this market varies substantially with the general market conditions.
Keywords: G2; D4; E58; 330; repo; central counterparty; market microstructure; financial crisis